Correlation of premature births with periodontal diseases (Research, Society and Development, 2022)
Periodontics is the most common disease occurring among humans; about 5% of the world population is affected. In pregnant women, specifically, these rates are relatively higher. The objective of this paper is to correlate periodontal disease with preterm birth. According to the High Risk Pregnancy Manual, preterm birth is defined by a gestational age of 22 (or 154 days) to 37 (259 days) weeks. The exact cause of preterm birth is still a mystery, but high rates of periodontitis have led researchers to become interested in the subject. Scientific articles from 2004 to 2022 were reviewed, based on Scielo, Google Scholar and Revista Odontológica da Unesp, with the following words: Premature birth, periodontal disease and correlation between periodontal disease and premature birth. The vast majority of articles correlated premature births and periodontal disease, because they believe that periodontitis itself generates inflammatory mediators that fall into the bloodstream and bind to the uterine walls, leading to uterine contraction. It is worth noting that the cause is hypothetical, and still needs to be extensively studied, to accurately state this correlation.